Surface circulation at the Strait of Gibraltar: A combined HF radar and high resolution model study. Issue 3 (28th March 2016) - Soto‐Navarro, Javier; Lorente, Pablo; Álvarez Fanjul, Enrique; Carlos Sánchez‐Garrido, Jose; García‐Lafuente, Jesús
Abstract: Observations from a high frequency radar system and outputs from a high resolution operational ocean model working at the Strait of Gibraltar have been analyzed and compared during the period February 2013 to September 2014 in order to evaluate their capability to resolve the surface circulation of the region. The description of the mean circulation patterns has been statistically assessed, showing good agreement, particularly in the central region of the strait corresponding with the Atlantic Jet (AJ) stream, although some short scale features are not reproduced by the model. In the frequency domain very high concordance is observed. Tidal maps of diurnal and semidiurnal constituents are in good agreement with previous observations. The analysis of the model and radar response to the wind forcing reveals that the low resolution of the model wind‐forcing field and its deeper superficial level smoothes the wind effect on the simulated currents. The first three EOF modes account for the 86% of model and radar variances. The coincidence between the observed and simulated patterns is very significant for the first two modes, which account for the mean velocity field and the latitudinal shifting of the AJ consequence of the flow‐topography interaction. The third mode captures the wind‐induced circulation, and greater discrepancies are found in this case. Results underline the complementary character of both systems: radar observations improve the model description, resolving short scale processes, while the model completes the radar information when the time or spatial coverage is poorer. Key Points: Surface circulation at the Strait of Gibraltar HF radar and model intercomparison Operational observatory system